Learning Path EXOOCO-2R Model in E-Module Based Reading and Writing Learning with Formative Assessment Tools - Anisah, Giati; Wulandari, Pramesti; Faqih, Fiyan Ilman; Madzalan, Julia Binti (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
Literacy is the foundation of education; it allows students to understand, evaluate, and communicate information effectively. However, many challenges arise in developing these skills, including limited access to adequate reading materials, ineffective teaching methods, and insufficient support and motivation from the surrounding environment. This research aims to develop a learning path in literacy learning, especially reading-to-write, based on e-modules with formative assessment tools. The development of learning paths in e-module-based reading-to-write learning with formative assessment tools is carried out using the ADDIE development model. This research began with a needs analysis to identify gaps in literacy learning. The e-module design and formative assessment tools are designed to provide a clear structure and continuous feedback to students. Based on the results of the research that has been carried out, it can be seen that the feasibility test results obtained an average value of 95.14%. These results show that the EXOOCO-2R learning path, formulated as an e-module, is considered very suitable for use, and this is in line with students' positive response to the learning path, with 68% included in the good category.